Medical students as diabetes educators - Smitha Bhat; K Sudeep (Wolters Kluwer Medknow Publications, 2017)
Introduction: As in all chronic diseases, an important component of care in diabetes is patient education (diabetes self-management education). Many diabetic care programs have shown that using specially trained diabetes educators - nurses, allied health-care professionals - improves outcomes. In India too, the National Defense Education Program has trained graduates to be diabetes educators. We wanted to use the strength of our institute - an intelligent and motivated student body to function as a diabetes educator. We developed a module to train medical students to be effective diabetes educators. The objective of this was twofold: First, to enhance patient self-management of diabetes; second, studies have shown that even among doctors, lack of knowledge about practical diabetes management was common. We believed that in view of the impending diabetes epidemic in India, it is important that every newly graduating MBBS doctor has sufficient knowledge about diabetes to counsel and manage patients at the primary care level. Materials and Methods: A physician and an endocrinologist developed patient and student training modules. Modules were administered to students by the authors and to patients by the trained students. Improvement in knowledge and attitudes was assessed by improvement in posttest scores and by qualitative analysis of the patient and student feedback. Results: We found that patient knowledge about diabetes and its management improved after contact with the diabetes educator as assessed by a marked increase in posttest scores. Students found that training patients in diabetes care improved the depth and range of their knowledge about diabetes and its management. This method of using students as diabetes educators facilitates both patient and trainer learning. Students who worked with patients using this module noted patient questions and suggested additional points of interest be covered in the module based on patient questions. We are currently incorporating these points into the module. We believe that this module on practical management of diabetes can be included in the curriculum for MBBS students in our university. Conclusion: Using medical students as diabetes educators improves student knowledge and patient self management of diabetes